Carbon nanotube-reduced graphene oxide fiber with high torsional strength from rheological hierarchy control - Wonsik Eom (Nature Portfolio, 2021)
Fibers with high torsional strength are of practical interest for artificial muscles, electric generators, actuators, etc. Here, the authors optimize torsional strength by overcoming rheological thresholds of nanocarbon (nanotube/graphene oxide) dopes.